1998
DOI: 10.1108/eum0000000006759
|View full text |Cite
|
Sign up to set email alerts
|

Small firm success and the art of orienteering: the value of plans, planning, and strategic awareness in the competitive small firm

Abstract: There is an ongoing debate within the academic literature about the value of the business plan in the development of the small firm. On closer inspection of the research, there appear to be clear benefits in the use of business planning as a process within the smaller business. This is in contrast to the production of a business plan as an output focused predominantly on convincing and acquiring resources from other organisations and individuals.\ud \ud As a process, business planning can be both formal and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 0 publications
4
67
0
1
Order By: Relevance
“…We measure the existence and extent of SP processes using a multiple variable scale. The Considering Response 1, the production of a formal statement of business objectives-such as plans and mission statements-is normally regarded as an essential feature of strategic planning (Campbell & Yeung, 1991;Hannon & Atherton, 1998). Such a statement could then be used to construct detailed objectives that shape and guide the operations of the firm; however, crucial to the strategic planning process are other planning practices that imply that a written strategic plan alone is a necessary but insufficient condition of strategic planning (Beaver & Ross, 2000;Hannon & Atherton, 1998).…”
Section: Independent Variablesmentioning
confidence: 99%
“…We measure the existence and extent of SP processes using a multiple variable scale. The Considering Response 1, the production of a formal statement of business objectives-such as plans and mission statements-is normally regarded as an essential feature of strategic planning (Campbell & Yeung, 1991;Hannon & Atherton, 1998). Such a statement could then be used to construct detailed objectives that shape and guide the operations of the firm; however, crucial to the strategic planning process are other planning practices that imply that a written strategic plan alone is a necessary but insufficient condition of strategic planning (Beaver & Ross, 2000;Hannon & Atherton, 1998).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Lybaert (1998) discovered that SME owners or managers with a greater strategic awareness use more information and that SMEs that use more information are generally more successful. Hannon and Atherton (1998) further revealed that for SMEs success is correlated with higher levels of strategic awareness and better planning of owners-managers. In addition, there is evidence to believe that companies that make strategic rather than just financial business plans perform significantly better financially than those that do not (O'Regan and Ghobadian 2004;Smith 1998).…”
mentioning
confidence: 96%
“…It is critical to both business management and planning process to understand the environment in which small business operates (Hannon & Atherton, 1997). By the external environment focus business firms can adapt market change and these enterprises have been recognized as prospector adaptive businesses (Wright, Kroll, Pray, & Lado, 1995).…”
Section: External Environment Analysismentioning
confidence: 99%
“…The visionary under-achiever has difficulty in translating the opportunities generated by high strategic awareness capacity into business development activity and because of poor planning effectiveness (Hannon & Atherton, 1997). Strategic planning includes developing vision and mission statements, performing internal (looking at the strengths and weaknesses) and external (looking at the opportunities and threats) audit establishing long term objectives and then generate and select better strategies (David, 2013).…”
Section: Vision Statementmentioning
confidence: 99%